Description in Dilshad Kawani’s novel (On the Way) - Talaat Mohammad Azeez; Hawkar Jameel Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research is entitled (Description in Dilshad Kawani’s novel (Baregawa). Description is one of the aspects that writers often turn to further explain and continue the plot and events, and further describe places and characters. This is more to expand scope of the novel and requires more information about events, characters and places. The novelist has successfully dealt with this technique in the novel, successfully describing various events, scenes, places, characters and psychological aspects of the characters, and dealing with the different types of description, that in each type of description, he has exposed interesting and expressive narrations. Thus, each of these expressions has given the novel a different style, which is more related to the novelist’s ability, feelings and behavior than how to deal with the tools of language. Therefore, he has been able, with these different descriptions, to create beauty and attractive content in the novel, and attract readers’ attention in such a way that makes the reader to see, with each different description, different, fresh and interesting scene and to expect descriptions and scenes that are more different. This forces readers to continue reading up to the end of the story. Here, we have tried, with a technical analysis approach, to analyze description and identity the most important types of analyses used in the novel.